2005
DOI: 10.1529/biophysj.105.064030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ion-Binding and Chemical Phospholipid Structure on the Nanomechanics of Lipid Bilayers Studied by Force Spectroscopy

Abstract: The nanomechanical response of supported lipid bilayers has been studied by force spectroscopy with atomic force microscopy. We have experimentally proved that the amount of ions present in the measuring system has a strong effect on the force needed to puncture a 1,2-dimyristoyl-sn-glycero-3-phosphocholine bilayer with an atomic force microscope tip, thus highlighting the role that monovalent cations (so far underestimated, e.g., Na(+)) play upon membrane stability. The increase in the yield threshold force h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
268
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(296 citation statements)
references
References 50 publications
24
268
1
2
Order By: Relevance
“…The above findings are in good agreement with experimental data [6][7][8][9] and with previously reported computational results. 6,12,15 It is, however, very instructive to consider the sensitivity of the results to a force-field employed for modeling salt ions.…”
Section: Resultssupporting
confidence: 93%
“…The above findings are in good agreement with experimental data [6][7][8][9] and with previously reported computational results. 6,12,15 It is, however, very instructive to consider the sensitivity of the results to a force-field employed for modeling salt ions.…”
Section: Resultssupporting
confidence: 93%
“…28,30 During the past decade, however, this view has been challenged. Indirect evidence from infrared spectroscopy, 32 fluorescence correlation spectroscopy, 33 atomic force microscopy, 35,36 smallangle X-ray diffraction, 41 spin-labeling electron paramagnetic resonance spectroscopy, 41 and calorimetric 33,41 studies suggest the possibility of Na + interacting with lipid carbonyl oxygens, binding lipids into complexes, and thus leading to detectable changes in area per lipid, bilayer thickness and rigidity, 41 as Hopping greatly promoted the lateral diffusion of Na + within the carbonyl region. The lateral mean squared displacement (MSD) of sodiums continuously complexed with DMPC (thick dashed red line) is considerably smaller than if lipid-free hops are allowed (thick continuous black).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that anionic 4, [22][23][24][25] and cationic 26,27 membranes interact readily with their counterions (especially divalent ones), whereas the interactions of zwitterionic lipid bilayers with salt ions appear rather sensitive to the size and valency of ions. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] As for molecular-level computational studies, the increase in computing power in the past few years has made it possible to extend computer simulations beyond the relatively long relaxation times of tens to hundreds of nanoseconds required for equilibration of ions in lipid/water systems. Although most computational studies by far have focused on the effects of salt ions on zwitterionic (neutral) lipid bilayers, 33,[42][43][44][45][46][47][48][49][50][51][52][53] there is also an increasing number of studies on anionic [54][55][56][57][58][59] and cationic 60,61 lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…These experiments, together with theoretical simulations [10], have led to the idea that individual ions may be interacting with multiple headgroups to form complex ''lipid-ion networks.'' This idea has been used to account for the observed influence of the ions such as enhanced mechanical strength of membranes [11] and reduced mobility of the lipid molecules therein [12].…”
Section: Direct Imaging Of Lipid-ion Network Formation Under Physiolomentioning
confidence: 99%
“…In fact, electrophoretic mobility measurements [32] and molecular dynamics simulations [30] have suggested that the binding coefficient of Na ions to PC headgroups is 0:15-0:6 M ÿ1 (2 -9 ions per 100 lipids for a 150 mM NaCl solution). However, it is also known that even such a small number of Na ions can significantly increase the mechanical strength of the bilayers with PC headgroups [11]. To reconcile these two results, Na ions associated with the membrane surface must be laterally moving to interact with a number of different headgroups.…”
Section: Direct Imaging Of Lipid-ion Network Formation Under Physiolomentioning
confidence: 99%